Intragenic anaplastic lymphoma kinase (ALK) rearrangements: Translocations as a novel mechanism of ALK activation in neuroblastoma tumors. Issue 2 (23rd September 2014) - Fransson, Susanne; Hansson, Magnus; Ruuth, Kristina; Djos, Anna; Berbegall, Ana; Javanmardi, Niloufar; Abrahamsson, Jonas; Palmer, Ruth H.; Noguera, Rosa; Hallberg, Bengt; Kogner, Per; Martinsson, Tommy
<x xml:space="preserve">Abstract</x> Anaplastic lymphoma kinase (ALK) has been demonstrated to be deregulated in sporadic as well as in familiar cases of neuroblastoma (NB). Whereas ALK‐fusion proteins are common in lymphoma and lung cancer, there are few reports of ALK rearrangements in NB indicating that ALK mainly exerts its oncogenic capacity via activating mutations and/or overexpression in this tumor type. In this study, 332 NB tumors and 13 cell lines were screened by high resolution single nucleotide polymorphism microarray. Gain of 2p was detected in 23% (60/332) of primary tumors and 46% (6/13) of cell lines, while breakpoints at the ALK locus were detected in four primary tumors and two cell lines. These were further analyzed by next generation sequencing and a targeted enrichment approach. Samples with both ALK and MYCN amplification displayed complex genomic rearrangements with multiple breakpoints within the amplicon. None of the translocations characterized in primary NB tumors are likely to result in a chimeric protein. However, immunohistochemical analysis reveals high levels of phosphorylated ALK in these samples despite lack of initial exons, possibly due to alternative transcription initiation sites. Both ALK proteins predicted to arise from such alterations and from the abnormal ALK exon 4–11 deletion observed in the CLB‐BAR cell line show strong activation of downstream targets STAT3 and extracellular signal‐regulated kinase (ERK) when expressed in PC12 cells. Taken together, our data indicate a novel, although rare, mechanism of ALK activation with implications for NB tumorigenesis. © 2014 Wiley Periodicals, Inc.